Clinical Value of the Assessment of Changes in MEP Duration with Voluntary Contraction - Brum, Marisa; Cabib, Christopher; Valls-Solé, Josep (Frontiers in Neuroscience, 2016)
Transcranial magnetic stimulation (TMS) gives rise to muscle responses, known as motor evoked potentials (MEP), through activation of the motor pathways. Voluntary contraction causes facilitation of MEPs, which consists of shortening MEP latency, increasing MEP amplitude and widening MEP duration. While an increase in excitability of alpha motorneurons and the corticospinal tract can easily explain latency shortening and amplitude increase, other mechanisms have to be accounted for to explain the increase in duration. We measured the increase in duration of the MEP during contraction with respect to rest in a group of healthy volunteers and retrospectively assessed this parameter in patients who were examined in a standardized fashion during the past 5 years. We included 25 healthy subjects, 21 patients with multiple sclerosis, 33 patients with acute stroke, 5 patients with hereditary spastic paraparesis, and 5 patients with signs suggesting psychogenic paresis. We found already significant differences among groups in the MEP duration at rest, patients with MS had a significantly longer duration, and patients with stroke had significantly shorter duration, than the other two groups. The increase in MEP duration during voluntary contraction was different in patients and in healthy subjects. It was significantly shorter in MS and significantly longer in stroke patients. It was absent in the five patients with suspected psychogenic weakness. In patients with HSP, an abnormally increase in duration occurred only in leg muscles. Our results suggest that the increase in duration of the MEP during contraction may reveal the contribution of propriospinal interneurons to the activation of alpha motorneurons. This mechanism may be altered in some diseases and, therefore, the assessment proposed in this work may have clinical applicability for the differential diagnosis of weakness.